The role of cellular senescence in tissue repair and regeneration. (September 2021) - Antelo-Iglesias, Lucía; Picallos-Rabina, Pilar; Estévez-Souto, Valentín; Da Silva-Álvarez, Sabela; Collado, Manuel
Highlights: The capacity to regenerate tissues varies widely along the animal kingdom and generally declines with aging of the organism. The accumulation of senescent cells in tissues during aging has been causally involved in their reduced function at old age. Cellular senescence plays a positive role as a morphogenetic force modelling and promoting tissue wound healing and repair. Work done on a wide range of organismal models is shedding light on this novel function of cellular senescence. Abstract: The capacity to regenerate damaged or lost tissue varies widely along the animal kingdom and generally declines with aging of the organism. The gradual accumulation of senescent cells in tissues during aging has been causally involved in their reduced function at old age, and to be at the basis of age-related diseases. Recently, however, cellular senescence has been shown to play a positive role as a morphogenetic force modelling and promoting tissue development during embryogenesis, and to be responsible for tissue wound healing and repair. Work done on organismal models ranging from fish and amphibians, with extraordinary regenerative capacities, to mammals, with a more restricted regenerative potential, is shedding light on a novel and unexpected function of cellular senescence. In this review, we will analyze the senescence phenotype and how could it be contributing or restricting tissue regeneration.